Business adventures : - Brooks, John (Open road, 1969)
Stories about Wall Street are infused with drama and adventure and reveal the machinations and volatile nature of the world of finance. Longtime New Yorker contributor John Brooks’s insightful reportage is so full of personality and critical detail that whether he is looking at the astounding market crash of 1962, the collapse of a well-known brokerage firm, or the bold attempt by American bankers to save the British pound, one gets the sense that history repeats itself.